(untitled) (Al-Mukhtar Journal of Basic Sciences, 2025)
Infectious diseases with a viral origin are of significant worldwide concern. In recent times, pandemics are creating havoc across the entire globe. This paper presents a constructive analysis of a new mathematical concept that will help medical authorities to predict and to take controlling measures. In this work, we use ordinary first-order differential equations and compartmental model analysis for the calculation of the infection rate, transmission rate, and reproduction number of the patients. A new Advanced Susceptible-Exposed-Infectious-Recovered model has been introduced, which has greater accuracy of the reproduction number. The prediction of a model of disease transmission demonstrates the performance characteristics of the proposed model.